2016
DOI: 10.2522/ptj.20150482
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Clinical Reasoning in Physical Therapy (SCRIPT): Tool for the Purposeful Practice of Clinical Reasoning in Orthopedic Manual Physical Therapy

Abstract: Clinical mentorship is a cornerstone of postprofessional training programs and intended to develop advanced clinical reasoning skills. However, clinical reasoning is often subconscious and, therefore, a challenging skill to develop. The use of a tool such as the SCRIPT may facilitate developing clinical reasoning skills by providing a systematic approach to data gathering and making clinical judgments to bring clinical reasoning to the conscious level, facilitate self-reflection, and make a mentored physical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Physical therapy residencies often use a number of methods geared at developing and assessing advanced clinical reasoning, with mentorship, regular reflective exercises, and objective assessment tools constituting these tactics. 6,7,12 As residency programs increase in popularity throughout the athletic training profession, a better understanding of how programs currently perceive, instruct, and assess advanced clinical reasoning is a pivotal first step to ensuring effective outcomes in residency education. This study sought to capture these answers through semistructured interviews with residency RPDs, and as a result, the 3 emergent themes were identified.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Physical therapy residencies often use a number of methods geared at developing and assessing advanced clinical reasoning, with mentorship, regular reflective exercises, and objective assessment tools constituting these tactics. 6,7,12 As residency programs increase in popularity throughout the athletic training profession, a better understanding of how programs currently perceive, instruct, and assess advanced clinical reasoning is a pivotal first step to ensuring effective outcomes in residency education. This study sought to capture these answers through semistructured interviews with residency RPDs, and as a result, the 3 emergent themes were identified.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has shown clinical mentorship to be effective in improving patient outcomes and clinician performance along with the development of practitioners' clinical reasoning capabilities. 12,22 It is no surprise that mentorship is a foundation of resident development. However, the application of clinical mentoring did differ between programs.…”
Section: Instructional Tacticsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the existing studies on CIMT do not especially emphasize on clinical reasoning, rather they give a straightjacket prescription of what should be done throughout the period of care whether the patients improve better or not. Clinical reasoning is important to physiotherapy practice [78]. The process of problem solving, clinical decision making, and clinical reasoning in constraint-induced movement therapy is represented in Figure 5.…”
Section: A Hypothetical Case To Help Enhance Problem Solving Clinicamentioning
confidence: 99%
“…It can be used to teach clinical reasoning skills and may facilitate a critical appraisal of why and how decisions are made [11]. Since mentoring and reflection are regarded as important instruments to facilitate the progression of clinical reasoning skills in HPs, several tools for guided mentorship and reflection have been developed to date [11,19,20]. As far as we know, our strategy is the first that specifically addresses clinical reasoning related to exercise therapy in patients with a complex health status.…”
Section: Case Knee Osteoarthritis 64 Years Old Womanmentioning
confidence: 99%